Kontrol Pintu Berbasis Android dan Arduino Uno Melalui Bluetooth Hc-06 - Ewi Ismaredah; Agung Justika (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2015)
Door is an important security for house owner. Door is parts of home that can’t be forget about design development and security. Now technology is evolved, Android and Arduino can be used many system, one of that system is a security. In the security system Android can be used as a media for giving an order to open, close, or lock the door. Arduino can be used in security system to execute the order that given. For the media that used to connecting both of device that can be using Bluetooth device. Using this door control that hoped to solve several problem like lost door key and controling a door with supported range.Keywords: Android, Arduino, Bluetooth, Door Control